2006
DOI: 10.1016/j.exer.2005.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on gene silencing by siRNAs: Implications for silencing in the anterior chamber of the eye

Abstract: Gene silencing by siRNAs offers the potential for reducing the expression of mutated genes that cause disease. It has been shown that the folding or secondary structure of a specific mRNA was significantly correlated to the silencing observed. Since this base pairing is dependent on free energy, the temperature of the cells may influence the effectiveness of a particular siRNA. The aqueous humor of the human eye has been measured to be around 34°C with the lens acting as a thermal barrier in the eye. The trabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Upon cold treatment, silencing of the GsVQ22 transgene was reduced, leading to increased expression of the transgene and enhanced growth inhibition of transgenic plants ( Figs 10 and 11 ). Temperature-sensitive gene silencing has been reported in both animals and plants 46 47 48 49 50 51 . In addition, the general levels of DNA methylation are reduced in plants at low temperature and gene silencing is less efficient 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Upon cold treatment, silencing of the GsVQ22 transgene was reduced, leading to increased expression of the transgene and enhanced growth inhibition of transgenic plants ( Figs 10 and 11 ). Temperature-sensitive gene silencing has been reported in both animals and plants 46 47 48 49 50 51 . In addition, the general levels of DNA methylation are reduced in plants at low temperature and gene silencing is less efficient 52 .…”
Section: Discussionmentioning
confidence: 99%
“…As for sNRT2.3-1, the temperature shifts from 25° to 32°C changed the hairpin loop sequences from UGUUGGAGAUGGAG into GAUGGA ( Fig. 5, A and D ), which would affect the binding to the target mRNA ( 14 , 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…The dry samples were ground to powder, and about 1 mg of the powder of each sample was analyzed using a DELTA V Advantage isotope mass spectrometer. Influx of 15 NO 3 − was calculated from the 15 N concentrations of the roots. sRNA structure predictions 3D models for sRNAs were built at 25° and 32°C using the Build Biopolymer module of Schrödinger software Suite 2022-1.…”
Section: Determination Of Nitrogen Uptake Using 15 Nmentioning
confidence: 99%
“…al. 23 have found that silencing could be effected by temperature. Lu and Mathews 9 account for the differences in equilibrium consideration when designing siRNAs and antisense oligodeoxynucleotides.…”
Section: Introductionmentioning
confidence: 99%